Fuzzy synthetic approach for seismic risk assessment of bridges with insights from the 2023 Kahramanmaras Earthquake in Turkiye - Abdullah Ansari; Ayed E. Alluqmani; Zhongkai Huang; Jong-Han Lee; Gürkan Özden; Yewuhalashet Fissha; Taoufik Saidani; Anas Ansari (Scientific Reports)
Abstract This paper leverages data from February 6, 2023, Kahramanmaras (Turkiye) Earthquake (Mw 7.8) to evaluate seismic risk and assess bridge damage through a fuzzy synthetic approach (FSA). A novel hierarchical damage classification framework is introduced, integrating critical factors such as ground conditions, structural characteristics, and seismic intensity. By analyzing data from 331 bridges affected by eight major historical earthquakes, the study underscored the influence of foundation depth, construction quality, and distance to fault rupture on structural resilience. Notably, 65% of damaged bridges were within 40 km of the distance to fault rupture, with oblique span orientations (45° to 65°) showing heightened susceptibility to seismic forces. To enhance resilience against earthquakes, the findings advocated for the adoption of deep foundations, advanced materials, and optimized structural designs. Consistent with field observations, the study reinforces the utility of FSA in enabling informed decision-making for disaster risk mitigation and is also beneficial for future seismic resilience design of bridges.